Prenatal zinc prevents communication impairments and BDNF disturbance in a rat model of autism induced by prenatal lipopolysaccharide exposure - Kirsten, Thiago B. [UNESP]; Queiroz-Hazarbassanov, Nicolle; Bernardi, Maria M. [UNESP]; Felicio, Luciano F. (Elsevier B.V., 2015)
Aims: Previous investigations by our group have shown that prenatal exposure to lipopolysaccharide (LPS), which mimics infections by Gram-negative bacteria, induced autistic-like behavior. No effective treatment yet exists for autism. Therefore, we used our rat model to test a possible treatment for autism. We selected zinc as the prenatal treatment to prevent or ease the impairments induced by LPS because LPS induces hypozincaemia. Materials and methods: We evaluated the effects of LPS and zinc on female reproductive performance. Communication, which is impaired in autism, was tested in pups by ultrasonic vocalizations. Plasma levels of brain-derived neurotrophic factor (BDNF) were determined because it has been considered an autism important biomarker. Key findings: Prenatal LPS exposure reduced offspring number and treatment with zinc prevented this reduction. Moreover, pups that were prenatally exposed to LPS spent longer periods without calling their mothers, and posttreatment with zinc prevented this impairment induced by LPS to the same levels as controls. Prenatal LPS also increased BDNF levels in adult offspring, and posttreatment with zinc reduced the elevation of BDNF to the same levels as controls. Significance: BDNF hyperactivity was also found in several studies of autistic patients. Together with our previous studies, our model of prenatal LPS induced autistic-like behavioral, brain, and immune disturbances. This suggests that it is a valid rat model of autism. Prenatal zinc prevented reproductive, communication, and BDNF impairments. The present study revealed a potential beneficial effect of prenatal zinc administration for the prevention of autism with regard to the BDNF pathway. (c) 2015 Elsevier Inc. All rights reserved.
Keywords: Autistic-like effects; Maternal immune activation; Prenatal infection; Ultrasonic vocalizations; Gestation